The therapeutic targets and signaling mechanisms of ondansetron in the treatment of critical illness in the ICU - Tao, Lili; Zhang, Zhenhui; Li, Chuang; Huang, Minxuan; Chang, Ping (Frontiers in Pharmacology, 2024)
Background: There is accumulating evidence regarding the benefits of the 5-HT3 receptor antagonist ondansetron for the treatment of critical illness due to its potential anti-inflammatory effect. This study attempted to determine the potential targets and molecular mechanisms of ondansetron's action against critical illnesses. Methods: A bioinformatics analysis of network pharmacology was conducted to demonstrate screening targets and the signaling pathways of ondansetron action against the most common critical illnesses such as acute kidney injury (AKI), sepsis, and acute respiratory distress syndrome (ARDS). Experiments of LPS-stimulated rat neutrophils with ondansetron treatment were conducted to further validate the relevant hypothesis.Results: A total of 198, 111 and 26 primary causal targets were identified from the data for the action of ondansetron against AKI, sepsis, and ARDS respectively. We found that the pathway of neutrophil extracellular traps (NETs) formation is statistically significantly involved in the action of ondansetron against these three critical illnesses. In the pathway of NETs formation, the common drug-disease intersection targets in these three critical illnesses were toll-like receptor 8 (TLR8), mitogen-activated protein kinase-14 (MAPK14), nuclear factor kappa-B1 (NFKB1), neutrophil elastase (NE), and myeloperoxidase (MPO). Considering these bioinformatics findings, we concluded that ondansetron anti-critical illness effects are mechanistically and pharmacologically implicated with suppression of neutrophils-associated inflammatory processes.It was also showed that after treatment of LPS-stimulated rat neutrophils with ondansetron, the key proteins NE, MPO, and Peptide Arginine Deaminase 4 (PAD4) in the NETs formation were significantly reduced, and the inflammatory factors IL-6, IL-1β, TNF-α, and chemokine receptor (CXCR4) were also significantly decreased.Conclusions: The excessive formation of NETs may have important research value in the development and progression of critical illness. Ondansetron may reduce excessive inflammatory injury in critical diseases by reducing the formation of NETs via influencing the five targets: TLR8, NFKB1, MAPK14, NE, and MPO. Ondansetron and these primary predictive biotargets may potentially be used to treat critical illness in future clinical practice.